Determinants of MSME Tax Compliance: The Role of Readiness for Coretax Implementation and Tax Literacy - Faradiba Magfirah; Ni Made Suwitri Parwati (Lembaga Riset Ilmiah, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) is essential for strengthening government revenue and supporting sustainable economic development. Although previous studies have extensively examined earlier digital tax services such as e-Filing, e-Billing, and e-SPT, limited empirical evidence is available regarding the newly implemented Core Tax Administration System (Coretax), which integrates all tax administration processes into a single digital platform and requires greater taxpayer readiness. This study addresses this research gap by examining the effects of Coretax implementation readiness and tax literacy on MSME tax compliance in Palu City, Indonesia. A quantitative survey was conducted involving 91 MSME taxpayers, selected through purposive sampling from a population of 1,076 registered taxpayers. Data were analyzed using multiple linear regression. The findings reveal that Coretax implementation readiness and tax literacy each have a positive and significant effect on MSME tax compliance and jointly contribute to improving voluntary compliance. These results indicate that successful digital tax administration depends not only on technological innovation but also on taxpayers' preparedness and understanding of tax regulations. Theoretically, this study extends the Theory of Planned Behavior by conceptualizing Coretax implementation readiness as a manifestation of perceived behavioral control within the context of integrated digital tax administration. Practically, the findings provide evidence for the Directorate General of Taxes to strengthen taxpayer training, digital mentoring, and tax literacy programs to support the effective implementation of Coretax and improve voluntary tax compliance among MSMEs.